Discover new perspectives and gain insights with IDNLearn.com. Our platform offers detailed and accurate responses from experts, helping you navigate any topic with confidence.
Sagot :
To solve the system of linear equations:
[tex]\[ \begin{cases} -7x + 6y = 5 \\ 7x + 2y = 11 \end{cases} \][/tex]
we can use various methods such as substitution, elimination, or matrix methods. Here's a detailed, step-by-step solution using the elimination method:
1. Set Up the Equations:
[tex]\[ \begin{aligned} \text{Equation 1:} & \quad -7x + 6y = 5 \\ \text{Equation 2:} & \quad 7x + 2y = 11 \end{aligned} \][/tex]
2. Add the Equations:
First, observe that adding both equations will eliminate [tex]\( x \)[/tex] since the coefficients of [tex]\( x \)[/tex] are opposites ([tex]\(-7x\)[/tex] and [tex]\(7x\)[/tex]).
[tex]\[ (-7x + 6y) + (7x + 2y) = 5 + 11 \][/tex]
Simplifying this, we get:
[tex]\[ 8y = 16 \][/tex]
3. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{16}{8} \][/tex]
[tex]\[ y = 2 \][/tex]
4. Substitute [tex]\( y \)[/tex] back into One of the Original Equations:
Use Equation 2 to find [tex]\( x \)[/tex]:
[tex]\[ 7x + 2(2) = 11 \][/tex]
Simplify the equation:
[tex]\[ 7x + 4 = 11 \][/tex]
[tex]\[ 7x = 11 - 4 \][/tex]
[tex]\[ 7x = 7 \][/tex]
[tex]\[ x = \frac{7}{7} \][/tex]
[tex]\[ x = 1 \][/tex]
5. Solution:
The solution to the system of equations is:
[tex]\[ x = 1 \quad \text{and} \quad y = 2 \][/tex]
Therefore, the point [tex]\( (x, y) \)[/tex] that satisfies both equations is [tex]\((1, 2)\)[/tex].
[tex]\[ \begin{cases} -7x + 6y = 5 \\ 7x + 2y = 11 \end{cases} \][/tex]
we can use various methods such as substitution, elimination, or matrix methods. Here's a detailed, step-by-step solution using the elimination method:
1. Set Up the Equations:
[tex]\[ \begin{aligned} \text{Equation 1:} & \quad -7x + 6y = 5 \\ \text{Equation 2:} & \quad 7x + 2y = 11 \end{aligned} \][/tex]
2. Add the Equations:
First, observe that adding both equations will eliminate [tex]\( x \)[/tex] since the coefficients of [tex]\( x \)[/tex] are opposites ([tex]\(-7x\)[/tex] and [tex]\(7x\)[/tex]).
[tex]\[ (-7x + 6y) + (7x + 2y) = 5 + 11 \][/tex]
Simplifying this, we get:
[tex]\[ 8y = 16 \][/tex]
3. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{16}{8} \][/tex]
[tex]\[ y = 2 \][/tex]
4. Substitute [tex]\( y \)[/tex] back into One of the Original Equations:
Use Equation 2 to find [tex]\( x \)[/tex]:
[tex]\[ 7x + 2(2) = 11 \][/tex]
Simplify the equation:
[tex]\[ 7x + 4 = 11 \][/tex]
[tex]\[ 7x = 11 - 4 \][/tex]
[tex]\[ 7x = 7 \][/tex]
[tex]\[ x = \frac{7}{7} \][/tex]
[tex]\[ x = 1 \][/tex]
5. Solution:
The solution to the system of equations is:
[tex]\[ x = 1 \quad \text{and} \quad y = 2 \][/tex]
Therefore, the point [tex]\( (x, y) \)[/tex] that satisfies both equations is [tex]\((1, 2)\)[/tex].
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. For dependable answers, trust IDNLearn.com. Thank you for visiting, and we look forward to helping you again soon.